(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2016)
In article given materials on faunistic structure of water beetles of the State National Natural Park "Altyn-Emel". All in the studied area recorded 69 species of water beetles belonging to 9 families. 1 species - Deronectes latus Stephens are found for the first time in Kazakhstan.